2009
DOI: 10.1007/s10591-009-9104-8
|View full text |Cite
|
Sign up to set email alerts
|

The Associations Between Intensive Residential Couple Therapy and Change in a Three-Year Follow-Up Period

Abstract: This Norwegian couple therapy effectiveness therapy study explored the course and prediction of relationships between depressive symptoms, interpersonal problems, and dyadic adjustment during residential treatment and over a 3-year post-treatment period (N = 117). All measures indicated significant improvement (p \ .001) between admission and discharge (effect sizes .25 to .67), and improvement was maintained at 3-year followup. The proportion of recovered patients during treatment was stable at follow-up. Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Therefore, it should be investigated whether the results can be replicated in a clinical sample. Furthermore, one could examine whether IIP higherlevel scores can differentiate between patient groups or predict treatment outcome, as previously shown for the corresponding octants (Alden and Phillips, 1990;Pincus and Wiggins, 1990;Ruiz et al, 2004;Tilden et al, 2010). The IIP higher-level scores could be particularly interesting when personality disorders are investigated because personality disorders are greatly concerned with impairments in the interpersonal domain (Pincus and Wiggins, 1990).…”
Section: Limitations and Future Researchmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, it should be investigated whether the results can be replicated in a clinical sample. Furthermore, one could examine whether IIP higherlevel scores can differentiate between patient groups or predict treatment outcome, as previously shown for the corresponding octants (Alden and Phillips, 1990;Pincus and Wiggins, 1990;Ruiz et al, 2004;Tilden et al, 2010). The IIP higher-level scores could be particularly interesting when personality disorders are investigated because personality disorders are greatly concerned with impairments in the interpersonal domain (Pincus and Wiggins, 1990).…”
Section: Limitations and Future Researchmentioning
confidence: 97%
“…The two circumplex For all following analyses of reliability and validity of IIP higher-level scores, we used the scoring model implied by the two scoring methods. We computed regression-component loadings of the scoring models (Schönemann and Steiger, 1976;Beauducel, 2005) as…”
Section: Reliability and Validity Of Iip Higher-level Scoresmentioning
confidence: 99%
“…As discussed extensively in the individual therapy literature (e.g., Kazdin, 2008), therapy delivered as part of research-based clinical trials often differs substantially from treatment-as-usual interventions delivered in the community. Within the couple therapy literature, the limited research on treatment-as-usual couple therapy suggests that effects may differ somewhat across settings, with small (Hahlweg & Klann, 1997) to medium (Anker, Duncan, & Sparks, 2009; Klann, Hahlweg, Baucom, & Kroeger, 2011) effect sizes on global relationship satisfaction found in general community clinics and medium to large effect sizes on global relationship satisfaction shown in more specialized clinics (Doss et al, 2012; Tilden, Gude, Sexton, Finset, & Hoffart, 2010).…”
mentioning
confidence: 99%
“…Given the lack of clinical evidence supporting IRT, the length of treatment for the study was somewhat arbitrary. A review of couples therapy research literature indicated that 12 sessions was the mode number of sessions for couples (Fals-Stewart, Birchler, & O'Farrell, 1996;Greenberg, Warwar, & Malcolm, 2010;Schade et al, 2014;Tilden, Gude, Sexton, Finset, & Hoffart, 2009;Trudel et al, 2008). This was a number also frequently suggested by IRT therapists with whom we consulted and fit within our research budget.…”
Section: Procedures and Measuresmentioning
confidence: 84%